THE GLOBAL MARKETS FOR CRUDE OIL AND THE EXTENT OF THE DOMINANCE OF THE SEVEN MAJOR COMPANIES (THE SEVEN SISTERS) OVER IT - Alyaa Suhail Najm (Scholar Express Journals, 2022)
As the global oil market changes its structure to include the increasing importance of the world's major crude oil companies, the role of these companies becomes the importance and the control of crude oil supplies. If the world's major oil companies had greater portions of actual and potential crude oil reserves, production, exploration and development activities, and if they had greater ability to use these resources, private IOCs would dominate the global oil industry outside North America and the former Soviet Union. This was the case in each of the main sectors of the industry: upstream (crude oil production), downstream (refining and marketing of products), and the middle sector (oil transportation). After 1970, this dominance was gradually substituted by the growing role of the national oil companies established by the major exporting countries (OPEC), which controlled their oil and gas reserves. Beginning in the early 1990s, IOCs responded by developing a more sophisticated business model aimed at maximizing shareholder value by creating and proving more reserves, while reducing costs. However, in the past fifteen years this business model has become increasingly ineffective. This was reflected in the generally weak performance of the shares of international oil companies relative to the global stock markets during this period, and in their financial performance in terms of profits and return on capital. As a result, their longterm prospects have become even more uncertain.
Keywords: Global Markets; Changes; Importance; Commodity And Energy